Insidious invisibilities: World literature, "race" and resistance - Medeiros, Paulo de (2021)
This chapter looks into how the debate around issues of race and racism is balanced between political and historical contexts that at times promote their absence, and, at others, imply a return to a thinking that is deeply committed to the more underground roots and dynamics of racial and racialising logics. In the body of the author’s reflection, the works analysed help in exercising a memory duty about contemporary human experiences and that, as the author notes, recognising the intense damage wrought by racism and other causes of the profound inequality that limits all of our potential to be human and free, and extolling the capacity for literature to help us in the never-ending process of becoming and belonging, is certainly not a new theory of world literature, but could, or should, be one of its main tasks.